Systematic characterization and comparison of the CYP2C9 variability of the Orang Asli in Malaysia with 12 populations. Issue 4 (August 2016) - Teh, Lay Kek; Subramaniam, Vinothini; Tuan Abdu Aziz, Tuan Azlin; Lee, Lian Shien; Ismail, Mohamed Izwan; Yu, Choo Yee; Ang, Geik Yong; James Johari, Richard; Ismet, Rose Iszati; Sahak, Noor Saadah; Ahmad, Aminuddin; Rahman, Thuhairah Abdul; et al.
Abstract: We conducted a systematic characterization of CYP2C9 variants in 61 Orang Asli and 96 Singaporean Malays using the whole genome sequences data and compared the variants with the other 11 HapMap populations. The frequency of rs1057910 ( CYP2C9*3 ) is the highest in the Orang Asli compared to other populations. Three alleles with clinical implication were detected in the Orang Asli while 2 were found in the Singaporean Malays. Large numbers of the Orang Asli are predicted to have reduced metabolic capacity and therefore they would require a lower dose of drugs which are metabolized by CYP2C9. They are also at increased risks of adverse effects and therapeutic failures. A large number of CYP2C9 variants in the Orang Asli were not in the Hardy Weinberg Equilibrium which could be due to small sample size or mutations that disrupt the equilibrium of allele frequencies. In conclusion, different polymorphism patterns, allele frequencies, genotype frequencies and LD blocks are observed between the Orang Asli, the Singaporean Malays and the other populations. The study provided new information on the genetic polymorphism of CYP2C9 which is important for the implementation of precision medicine for the Orang Asli.